Analisis Geometrik Pada Ruas Jalan Gadihu Indah – Ahuru Kota Ambon - Fransiskus Idonggoleng; Julius Buyang; Penina T. Istia (Universitas Pahlawan Tuanku Tambusai, 2024)
This researct location is on the Gadihu Indah – Ahuru road Ambon City 1.300 km long with the coordinates of the starting point of the research location (n 1°19’43,7” e 124°54’13,3”) and the final point of the research location (n 1°20’44,5” e 124°53’53,9”). Which is located in Batu Merah Kebun Cengkeh Village to Ahuru Village, Sirimau Ambon Distrik, Maluku Province. The road is located on a plateau which has several bends and incline and the turning radius at intersections does not comply with Road Geometric Planning Standards, so accidents often occur. The aim of this research is to analyze more deeply in the form of a review of vertical and horizontal alignments, namely inclines, descents and bends. So that you get appropriate results in planning the road.The analysis method uses the AutoCAD Civil 3D Software program, which is determinet based on Road Geometric Planning Guidelines No.20/SE/Db/2021. The data type consists of primary data and secondary data. For primary data, road condition data and topographic data (measurements) and for secondary data, planned speed data. The analysis results show that the horizontal alignment has 17 types of Full Circle (FC) bends, namely at corners 1 to 6 and continued at corners 8 to 18. Spiral Cirle Spiral (SCS) bends have 1 type of band at corner 7. Then in the alignment the vertical has 20 vertical curves, with 11 convex verticals and 9 concave verticals.